2014
DOI: 10.1136/annrheumdis-2013-204655
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the anti-IL-12/23 p40 monoclonal antibody, ustekinumab, in patients with active psoriatic arthritis despite conventional non-biological and biological anti-tumour necrosis factor therapy: 6-month and 1-year results of the phase 3, multicentre, double-blind, placebo-controlled, randomised PSUMMIT 2 trial

Abstract: ObjectiveAssess ustekinumab efficacy (week 24/week 52) and safety (week 16/week 24/week 60) in patients with active psoriatic arthritis (PsA) despite treatment with conventional and/or biological anti-tumour necrosis factor (TNF) agents.MethodsIn this phase 3, multicentre, placebo-controlled trial, 312 adults with active PsA were randomised (stratified by site, weight (≤100 kg/>100 kg), methotrexate use) to ustekinumab 45 mg or 90 mg at week 0, week 4, q12 weeks or placebo at week 0, week 4, week 16 and crosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
394
2
28

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 590 publications
(441 citation statements)
references
References 34 publications
17
394
2
28
Order By: Relevance
“…First, patients with nonpsoriatic pSpA and patients with PsA both belong to the SpA group with predominant peripheral manifestations sharing common clinical and genetic features 1,2 . Second, the degree of improvements in enthesitis burden (mean change from baseline or percentage improvement or resolution of enthesitis) observed in our trial is comparable with that observed in patients with PsA 19,21,23 . Third, an imaging study comparing magnetic resonance imaging (MRI) and clinical examination showed similar enthesitis patterns (similar frequencies of enthesitis on MRI compared with clinical examination) in patients with PsA and SpA 27 .…”
Section: Rheumatologysupporting
confidence: 68%
See 2 more Smart Citations
“…First, patients with nonpsoriatic pSpA and patients with PsA both belong to the SpA group with predominant peripheral manifestations sharing common clinical and genetic features 1,2 . Second, the degree of improvements in enthesitis burden (mean change from baseline or percentage improvement or resolution of enthesitis) observed in our trial is comparable with that observed in patients with PsA 19,21,23 . Third, an imaging study comparing magnetic resonance imaging (MRI) and clinical examination showed similar enthesitis patterns (similar frequencies of enthesitis on MRI compared with clinical examination) in patients with PsA and SpA 27 .…”
Section: Rheumatologysupporting
confidence: 68%
“…The MASES showed inconsistent performance in terms of discriminatory properties in 3 trials of apremilast in PsA; no clear dose response was evident, and only 1 of 6 dose arms showed significant improvement versus PBO 18 . The lack of clear, evidence-based recommendations for enthesitis tools may explain the use of a modified MASES in a phase III trial of ustekinumab in PsA; in this version, the insertions of the plantar fascia-peripheral enthesitis sites were included along with the original MASES sites 19 . Using this PsA-modified MASES, ustekinumab 90 mg significantly improved enthesitis at Week 24 compared with PBO (median percentage change 48% vs 0%, respectively, p < 0.01) 19 .…”
Section: Rheumatologymentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase III PSUMMIT 1 trial, similar improvements were shown in PsA patients who were anti-TNF-experienced (78). In a PSUMMIT-2 phase III trial, data through week 60 indicated that ustekinumab induces long-term significant improvement in the joint, enthesitis/dactylitis and skin symptoms of active PsA (79). These findings supported the FDA approval of ustekinumab in the treatment of active PsA as of September 2013.…”
Section: Ustekinumabsupporting
confidence: 68%
“…Indeed, all 5 of the antibodies above have been demonstrated to be effective in skin psoriasis, and 2 (ustekinumab and secukinumab) have been approved in the United States for this indication 4,5,7,8,9 . Ustekinumab has also been approved for the treatment of PsA, and there have been studies demonstrating the effectiveness of brodalumab and secukinumab in this disease as well 10,11 .…”
Section: Rheumatologymentioning
confidence: 99%